REVOLUTIONARY WAVES N THE POST-SOVIET EXPANSE - ZHILTSOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2005)
The tempestuous events over the past two years in several CIS countries have led to the formation of a qualitatively new geopolitical, economic, and political situation in the post-Soviet expanse. Although the assessments of these events are largely emotional (some call the changes in power in Georgia, Ukraine, and Kyrgyzstan revolutions, others refer to them as coups), the general conclusion drawn is that all the former U.S.S.R. republics have entered a qualitatively new stage in their development. This new stage could end in the formation of an essentially different geopolitical reality and new political plots in each of the countries indicated. The situation which has developed in the Commonwealth states is, first, the result of the geopolitical rivalry among Russia, Europe, and the U.S. for domination throughout the expanses of the former Soviet Union, second, is caused by the economic struggle between competing groups within each country, and third, is generated by the people’s discontent with the authorities’ policy during the almost 15 years of their independence. Here it is important not to roll everything into one lump, but to look at the main causes of what happened, identify the laws governing them, and determine what awaits these republics in the future.